The ability of investors in the stock market to predict the financial failure of companies and its impact on the market’s financial performance indicators - (an applied study on a sample of companies listed on the Iraq Stock Exchange for the period from 2 - Haider Younis Al-Musawi,; Haider Abbas Abed Allah, (Iraqi Journal for Administrative Sciences, 2025)
Financial market represents a basic anchor in a country\'s economic sectors Advanced or Nami, and what is owned by sectoral Overlaps in all economic joints. The study examines the ability and the possibility of investors in the stock market on the use of financial ratios in the financial analysis and its role and importance in predicting the financial failure of the companies through the practical application of a number of listed companies in the Iraqi market for securities, as well as its impact on the financial performance indicators of the market. Two models have been used to predict the financial failure of the listed companies in the Iraqi market for securities, namely: - - Modified Altman Model. - Kida Model. The study is based on the following assumptions: - Lack of capacity and the possibility for investors traders in the stock market to predict the failure of financial firms. The aim of this study to several goals including: - Test some of the listed companies in the Iraqi market for securities to get to know the extent of their exposure to financial failure in the future. The study found a set of conclusions both in the theoretical or practical side is the most important: - Having a capacity for investors in the stock market to predict financial failure of the companies gives signals that prices deliberative of listed companies within the space fair pricing of shares of these companies because in the case of pricing more or less than the fair price, this drives investors in the market searching for the reasons that prompted to pricing Prices more or less to prevent tampering and conspiracy to other dealers. In light of these findings, the study recommended a number of recommendations, including: - Working attention analyzing financial ratios because of its importance in the development of important indicators on the status and drew the attention of companies based on those companies feasibility analysis of financial ratios them.